Cardiorespiratory responses to downhill versus uphill running in endurance athletes - Lemire, M.; Lonsdorfer-Wolf, E.; Isner-Horobeti, M.; Kouassi, B.; Geny, B.; Favret, F.; Dufour, S. (Research Quarterly for Exercise and Sport, 2018)
Purpose: Mountain running races are becoming increasingly popular, although our understanding of the particular physiology associated with downhill running (DR) in trained athletes remains scarce. This study explored the cardiorespiratory responses to high-slope constant velocity uphill running (UR) and DR. Method: Eight endurance athletes performed a maximal incremental test and 2 15-min running bouts (UR, +15%, or DR, -15%) at the same running velocity (8.5 ± 0.4 km/h). Oxygen uptake (VO2), heart rate (HR), and ventilation rates (VE) were continuously recorded, and blood lactate (bLa) was measured before and after each trial. Results: Downhill running induced a more superficial E pattern featuring reduced tidal volume (p < .05, ES = 6.05) but similar respiratory frequency (p > .05, ES = 0.68) despite lower VE (p < .05, ES = 5.46), VO2 (p < .05, ES = 12.68), HR (p < .05, ES = 6.42), and bLa (p < .05, ES = 1.70). A negative slow component was observed during DR for VO2 (p < .05, ES = 1.72) and HR (p < .05, ES = 0.80). Conclusions: These results emphasize the cardiorespiratory responses to DR and highlight the need for cautious interpretation of VO2, HR, and VE patterns as markers of exercise intensity for training load prescription and management.